THE APPLICATION OF JURISPRUDENTIAL INQUIRY LEARNING MODEL TO INCREASE STUDENT’S SOCIAL SKILLS AND LEARNING ACHIEVEMENT - Eva Yuliana; Johanes Sapri; Turdjai Turdjai (UNIB Press, 2017)
This study aims to (1) describe how the improvement of social skill ability through learning Model Jurisprudential Inquiry in social studies learning in grade V SDN 06 Pondok Kelapa (2) describe how the improvement of student achievement in learning social studies through learning Model Jurisprudential Inquiry in social studies learning in class V SDN 06 Pondok Kelapa (3) describes how the effectiveness of Learning Model Yurisprudential Inquiry to improve student achievement in learning social studies in class V SDN 06 Pondok Kelapa. The research is a classroom action research combined with quasi experiments. The subjects of this study are VA class students and VB SDN 06 Pondok Kelapa class as PTK and experimental class. While the class VC SDN 06 Pondok Kelapa, as a control class. The results of this study indicate that the application of learning yurisprudential inquiry model can: (1) improve social skills in social studies learning, (2) Application of learning model Jurisprudential Inquiry can improve achievement in learning social studies, (3) Effectiveness of application of learning model Jurisprudential Inquiry can improve student achievement on learning IPS class V SDN 06 Pondok Kelapa Keywords: learning model jurisprudential inquiry, social Skills, and learning achievement